Toward cost-effective nearly zero energy buildings: The Dutch Situation. (2nd October 2016) - Zeiler, Wim; Gvozdenović, Kristian; de Bont, Kevin; Maassen, Wim
Abstract : To reduce the high energy demand and pollution of greenhouse gasses of the built environment, the Energy Performance of Building Directive came in 2010 with plans for the European Union member states. Buildings must be, according the plan, nearly zero energy and should reach this goal by implementing cost-effective (passive-) measures for a high energy performance and application of sustainable energy source(s) for the remaining demand. In this research, a study is done on recently completed Dutch sustainable and nearly zero energy buildings, from which can be concluded that the goal from the Energy Performance of Building Directive now is rarely met. Most buildings use aquifer thermal storage system with a heat pump and thermal activated building systems. However, to really meet the nearly zero energy and low CO2 emissions goal, in 2019 for public buildings and 2021 for all buildings, more focus is needed from the design teams in the early design phase toward cost-effective solutions. Life cycle costs are an important decision driver for achieving a cost-effective, nearly zero energy building. A new method, which incorporates additional benefits as productivity increase, sick leave reductions, Public Relations, and higher renting value, reveals that then an "economic optimal nearly zero energy building" can be met easier in the near future.